Anatomical variations detected in the arterial arches of the palm: A case report - Laxman Khanal; Saroj Kumar Yadav (Janaki Medical College Journal of Medical Science, 2024)
Background and objectives: The vascular anatomy of the hand, particularly the superficial palmar arch (SPA) and deep palmar arch (DPA), presents complex and variable patterns crucial for microsurgical interventions. Presentation of case: We encountered a unique case during routine cadaveric dissection, an incomplete SPA in a male cadaver. The left upper extremity revealed atypical branching of the ulnar artery (UA), where the superficial branch lacked the typical connection to the radial artery, deviating from conventional SPA anatomy. The medial branch of UA served as a common trunk, supplying the common palmar digital artery and the digiti minimi artery. Additionally, origin of first common palmar digital artery from palmar metacarpal artery (branch of radial artery) instead from ulnar artery itself further distinguished this case. Discussion: Incomplete SPA due to absence of connection between ulnar artery and superficial branch of radial artery is also reported by other studies with prevalence ranging from 3.6 % to 21.7%. Knowledge of this type of variation is significant for hand surgeries involving harvesting of the radial artery to prevent dangerous complications like ischemia and gangrene. Conclusion: Understanding anatomical variations in hand vasculature is pivotal for surgical procedures. This case highlights the importance of thorough anatomical knowledge in clinical practice and surgical planning.